(untitled) (Physical Education, Health and Social Sciences, 2025)
An experiment was conducted to check the efficacy of botanical extracts and a synthetic insecticide against cabbage butterfly in cauliflower at farmer field in Charsadda during 2023-2024. Randomized complete block design was followed with 4 treatments via clove extract, ginger extract, moringa extract and spinosad and a control replicated 3 times. Result indicated that all the tested treatments found better than control against cabbage butterfly. However, Spinosad was found better in managing cabbage butterfly in both spray application. Spinosad showed maximum larval mortality (65.72 & 84.51) after first and second spray application. Among botanicals Ginger extract was comparatively better and had (51.08 & 73.34) larval mortality. The data also showed that yield was significantly higher in plot treated with spinosad (1080.3 kg/ha-1) followed by Ginger extract (935.0 kg/ha-1). The maximum cost benefit ratio (CBR) was recorded in Spinosad treated plot (1:6.58) and among the botanical the Ginger extract treated plot shows the maximum CBR (1:5.38). It was concluded in the absence of Spinosad, Ginger and Clove extract are the best alternative and can be used in IPM program against cabbage butterfly.